229. Breast Imaging Quality: Conventional Handheld Ultrasound versus Automated 3D Breast Ultrasound System. (December 2018) - Levrero, F.; Vaccara, E.M.L.; Guidasci, G. Rambaldi; Calabrese, M.; Dordolo, M.; Tagliafico, A.; Gristina, L.; Schiaffino, S.; Massone, A.M.; Piana, M.
Abstract : Purpose: Automated 3D Breast Ultrasound (ABUS) as an adjunct to mammography is promising technology in screening especially in women with dense breast parenchyma. We aim to inquire numerically imaging performance of Invenia ABUS (GE Healthcare, WI, USA) in comparison to conventional handheld Ultrasound (US), just to check their similar malignancy detection rates[1] . Methods: According to SIRM ( Società Italiana di Radiologia Medica [2] ), using a certified phantom it's possible to provide a general judgment on the operation of the equipment. So we used a rubber-based tissue mimicking material shown in the figure, UC-551M (ATS Laboratories). This phantom allows to investigate every kind of parameters (line targets, axial and lateral resolution, anechoic targets structures of different sizes and gray scale target structures). The phantom acquisitions were made in clinical mode: ABUS select automatically depth of penetration 3, 5/4/5 cm and frequency 10/9/8, 18 MHz depending on the size of the breast (small/medium/large); conventional US depth has been optimized in the range 4–5 cm and 7, 5–15 MHz by an experienced radiologist depending on the specific insert to display, as suggested by ATS Laboratory[3] . Results: The preliminary results are shown in the table. Displayed dynamic range is optimal for all the ultrasound scanners (coefficient of determination R 2 ⩾95%) and the maximum value is ABUS and Samsung score of 99%. Distance measures are coherent, there is no geometric distortion. The analysis of the Point Spread Function is underway with advanced mathematical methods. Conclusions: ABUS provides a 3D volume consisting of 330 trans-axial images, whose quality is generally comparable with US 2D images.